Recent advances and future challenges of four key resources cooperation in cognitive radio network - Xianzhong XIE; Ying LUO; Ke YAN; Jiujiu CHEN (Tongxin xuebao)
Cognitive radio (CR) can improve spectrum utilization by spectrum sharing or cooperation between the primary user and secondary users.It is well known that energy,interference and relay are also three key resources in cognitive radio network (CRN).Energy cooperation or sharing between the primary user and secondary user will further promote energy efficiency.Energy harvesting from RF interference signal can turn bane (interference) into a boon (green energy).Secondary user relay data of the primary user can enhance QoS of the primary user,also get some opportunities for their own transmission.Thus,four resources cooperation (spectrum,energy,interference,relay) in CRN will improve simultaneously both spectrum efficiency and energy efficiency,and also increase throughput and QoS.The overviews for collaborative utilization problems of four key resources in CRN was given.Firstly,collaboration models of four key resources were analyzed.Then,recent research advances were summarized,including three kinds of resources collaborative utilization (both energy harvesting and relay transmission,both energy cooperation and energy harvesting) and four resources collaborative utilization (simultaneous relay transmission,energy harvesting and energy cooperation) in CRN.Further,some potential challenges of four key resources cooperation in CRN were discussed.Finally,some key future research directions was concluded.